EFFECT OF SODIUM BISULFIT CONCENTRATION TO VITAMIN C RESIDENCE, TOTAL RESIDUAL SULFITE AND CONSUMER EQUIPMENT LEVEL ON HAIR SIRUP - Nani Ratnaningsih; Yuriani Yuriani (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
Effect of concentration of sodium bisulfite to vitamin C content, totalsulfite residue and consumer hedonic level of rambutan syrup has been studied. Research method was experiment by complete random design. Vitamin C content was analyzed by the iodium titration, the total sulfite residue by distillation analysis (Rangana, 1977), and consumer hedonic level by hedonic scale test with 80 untrained panelists. Analysis data was done by analysis variance at 5% level of significance and continued with the Tukey test. Based on research result showed that concentration of sodium bisulfite have a significant effect to vitamin C content and total sulfite residue of rambutan syrup. Vitamin C content and total sulfite residue increased with the increasing concentration of sodium bisulfite. Concentration of sodium bisulfite has a significant effect to aroma of rambutan syrup, otherwise no influence at color andflavor.